1979
DOI: 10.1002/oms.1210140409
|View full text |Cite
|
Sign up to set email alerts
|

Metastable ion studies. XII—Molecular and fragment ion structures for isomeric C4H6O2 acids

Abstract: Metastable peak characteristics, ionization and appearance energy data and isotopic labelling experiments have been applied to a study of the fragmentation behavioUr of the molecnlar ions of the isomeric C A O , acids, cis and trans-uotonic acids, methacrylic acid, butenoic acid and cydopropane carboxylic acid. Prior to the losses of H,O and CH,, all the metastable molecular ions rearrange to [cis-crotonic acid]+' ions. Loss of H,O, which generates a composite metastable peak, is proposed to yield vhylketene a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1982
1982
2006
2006

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…In the EI-spectrum, the fragment ion at m/z 478 shows the loss of water ([M À H 2 O] + ) described before in systems with a double bond in b-c-position to a carboxy group suggesting this fragmentation to take place at position C-28 (Lauwers et al, 1973;Herrmann and Schwarz, 1976;Holmes et al, 1979). The fragment ions m/z 423, 327 and 169 represent the loss of the chain C-1 to C-3 ([M À C 3 H 5 O 2 ] + ), the loss of the complete side chain C-20 to C-26 ([M À C 9 H 13 O 3 ] + ), and the loss of the triterpene skeleton at position 20 ([M À C 22 H 31 O 2 ] + ), respectively, due to r-fragmentation.…”
Section: Spongiporic Acid a 11mentioning
confidence: 78%
“…In the EI-spectrum, the fragment ion at m/z 478 shows the loss of water ([M À H 2 O] + ) described before in systems with a double bond in b-c-position to a carboxy group suggesting this fragmentation to take place at position C-28 (Lauwers et al, 1973;Herrmann and Schwarz, 1976;Holmes et al, 1979). The fragment ions m/z 423, 327 and 169 represent the loss of the chain C-1 to C-3 ([M À C 3 H 5 O 2 ] + ), the loss of the complete side chain C-20 to C-26 ([M À C 9 H 13 O 3 ] + ), and the loss of the triterpene skeleton at position 20 ([M À C 22 H 31 O 2 ] + ), respectively, due to r-fragmentation.…”
Section: Spongiporic Acid a 11mentioning
confidence: 78%
“…The above results permit further analysis of observations of the elimination of H 2 0 from ionised methacrylic acid (13) This proposal cannot be demonstrated by labelling experiments, but the CA mass spectrum of the ion-source generated [C4H40]+' ions from this reaction can most satisfactorily be reproduced from a 2:3 mixture of the CA mass spectra of [vinylketene]+' and the branched ketene.…”
Section: Ether Ionsmentioning
confidence: 80%
“…In an earlier study (13), it was concluded that [vinylketene]+' was the predominant tnlz 68 ion generated by the loss of H 2 0 from cis and trans crotonic acids and cyclopropanecarboxylic acid. However, the metastable peaks for these reactions were of composite shape and it was considered that the [C4H40]+' isomer ionised cyclobutenone might be cogenerated.…”
Section: Ether Ionsmentioning
confidence: 99%
“…the e-fission and the water loss [19][20][21][22][23] are absent in the EI mass spectra (Table 1). All compounds give molecular ion peaks.…”
Section: Resultsmentioning
confidence: 99%